2007
DOI: 10.1063/1.2409930
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical approach to evaluate thermodiffusion in aqueous alkanol solutions

Abstract: Flow due to thermodiffusion may change direction in fluid mixtures with the variation of composition and temperature. This occurrence remains an unraveled phenomenon in petroleum research. Using a modified theoretical approach, this paper evaluates the thermal diffusion factor in alkanol water mixtures, including methanol, ethanol, and isopropanol aqueous mixtures. By combining this approach with an equation of state perturbed chain statistical associating fluid theory and using two adjustable parameters calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Thermal diffusion in liquids is not so well understood even for binary mixtures [3][4][5][6]. One of the peculiarities of thermodiffusion in some aqueous solutions and organic mixtures is that the Soret coefficient may change sign depending on composition and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal diffusion in liquids is not so well understood even for binary mixtures [3][4][5][6]. One of the peculiarities of thermodiffusion in some aqueous solutions and organic mixtures is that the Soret coefficient may change sign depending on composition and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Two thermodynamic conditions have been studied, one corresponding to a dense liquid at T * =1 and ρ * =0.8 and the second one to a dense supercritical gas at T * =1.686 and ρ * =0.477 that was studied previously 14 The second mixture is a n-decane/methane (modelled by LJ spheres) one at T * =1.686 and ρ * =0.477 previously studied 15 . By using the SPTA, it has been found that Besides, it is worth noting that the possibility of obtaining the SP T α coefficient for such fluid mixtures, for both infinite dilution limits, could be valuable as well because recently proposed models to estimate thermodiffusion [41][42] uses these data to predict the thermodiffusion on the whole molar fraction range.…”
Section: Simple Fluidsmentioning
confidence: 99%
“…% of water concentration in ethanol. The water-ethanol mixture has a volumetric and thermal complex properties [18,19], and we would expect the refractive index changes with the volumetric concentration variation, which follows the binary liquid compounds theory [20]. The relative intensity increases with the increasing temperature values, limited by the pure solution of ethanol and pure water.…”
Section: Resultsmentioning
confidence: 97%